The causes of the digital divide in remote areas in the Sultanate of Oman and the measures that must be followed to narrow it during the spread of epidemics - Alkhatri, Mohammed Said; Al-Mousawi, Abdulmuttalib Sharaf; Alajmi, Mohammed Mubarak (Journal of Educational and Psychological Sciences, 2021)
This study aimed to determine the causes of the digital divide in remote areas and the procedures that must be followed to narrow it in the time of the spread of epidemics. Of the faculty members in distant schools, and the results of the study showed that the most reasons that led to the emergence of the digital divide in remote areas from the viewpoint of the sample members )227) were the social and cultural reasons, while the respondents indicated that the least reasons that led to the emergence of the digital divide in the regions The administrative reasons were as the results of the study showed that there are no statistically significant differences in the reasons leading to the emergence of the digital divide according to the difference of both sex (male/ ethnic) and the position (teacher/ administrator). The respondents' proposals indicated and confirmed that one of the most important procedures is from It may contribute to narrowing the digital divide between remote areas and the areas where digital services are available in the Sultanate. It is providing free internet and strengthening the network in expanding Anchor remote areas, providing each teacher and student with a device, in addition to the necessity to train teachers, students and parents on e-learning with a focus on educating students, parents and the community about the importance of e-learning.
Keywords: digital divide; distant schools; e-learning